Analysis of vaccinia virus transcriptional complexity in vitro and in vivo: characterization of RNase T1-resistant 5'-terminal oligonucleotides. - Whitkop, C (1982)
Vaccinia virus mRNAs synthesized in vitro and in vivo, polyadenylated leader sequences synthesized in vitro in the absence of added GTP, CTP, or UTP or in the presence of 20 micrograms of actinomycin D per ml, and high-molecular-weight RNA synthesized in vitro under limiting ATP concentrations were labeled specifically in the cap structure using [alpha-32P]GTP and vaccinia-soluble enzyme extracts. The complexity of RNase T1-resistant 5'-terminal oligonucleotides was analyzed by two-dimensional polyacrylamide gel electrophoresis. Approximately 190 unique T1-resistant 5'-terminal oligonucleotides were observed from vaccinia virus 8 to 12S RNA synthesized in vitro. A somewhat greater complexity was observed with polyadenylated leader sequences and actinomycin D RNAs where unique T1-resistant oligonucleotides ranged from approximately 210 to 280 5'-terminal fragments. On a composite fingerprint of the above RNAs, more than 300 identifiable unique T1-resistant 5'-terminal oligonucleotides were observed. Significantly, close to 300 T1-resistant fragments were derived from RNA sedimenting faster than 18S on denaturing sucrose gradients. Analysis of vaccinia RNAs synthesized in vivo in the absence of either de novo protein synthesis or DNA replication or in the presence of actinomycin D gave essentially similar profiles of 5'-terminal T1-resistant oligonucleotide fingerprints consisting of approximately 200 fragments. Analysis of the 5'-terminal T1-resistant oligonucleotides of vaccinia RNAs present after DNA replication showed essentially the same pattern of early T1-fragments albeit in reduced amounts but in addition revealed a complex pattern of T1-resistant oligonucleotides unique to this class of vaccinia RNA.